Genomic insights into five selected multidrug-resistant Pseudomonas aeruginosa isolated from Sodwana Bay, South Africa - Serepa-Dlamini, Mahloro Hope; Kondiah, Kulsum; Maumela, Pfariso; Ogofure, Abraham Goodness; Green, Ezekiel (Frontiers in Microbiology, 2025)
Pseudomonas aeruginosa (P. aeruginosa) is a common environmental organism and the leading cause of opportunistic human diseases. Its inherent tolerance to pharmaceuticals and disinfectants is fundamental to its pathogenicity. This study investigates the genomic characteristics of five multidrug-resistant Pseudomonas aeruginosa isolates from Sodwana Bay, South Africa, highlighting resistance profiles and virulence factors. Using Illumina MiSeq sequencing and functional annotation via Prokka, PATRIC and RAST, the analysis revealed significant resistance mechanisms. The isolates clustered with P. aeruginosa DSM 50071. The genome sizes for AF, AF1, BIS, BIS1, and BDPW, ranging from 7.0 to 6.4 Mb, were observed, with G + C contents ranging from 66.1 to 66.48%. A de novo multi-drug resistance was observed in all the tested strains, while β-lactamase resistance genes blaPAO, aminoglycoside phosphorylating enzymes genes aph(3′)-IIb, and fosfomycin resistance gene (fosA), were among the resistance genes found in all samples. The ST analysis revealed the presence of high-risk STs (ST244) in the genomes. The blaOXA50 gene linked to high-risk STs, which exhibits increased efficacy against carbapenems, was more common in most genomes. The examination of the virulome revealed that the exoS was more commonly found in most genomes, whereas the exoU was found in only two isolates. This study presents information concerning the genetic heterogeneity among P. aeruginosa strains obtained from various habitats and valuable insights into resistance gene distribution in environmental reservoirs.